South Africa's Financial Development and its Role in Investment - Brian Muyambiri; NM Odhiambo (Journal of Central Banking Theory and Practice, 2018)
This study investigates the impact of financial development on investment in South Africa between 1976 and 2014. The model estimated is based on the flexible accelerator investment model. Composite indices for bank-based and market-based financial development indicators are used as explanatory variables. The estimated model postulates that both bank-based financial development and market-based financial development have an accelerator-enhancing effect on investment. Results show that market-based financial development has a positive impact on investment in the long run, while bank-based financial development has a negative effect in the short run. Implications are that, for South Africa, market-based financial development has a positive accelerator-enhancing effect on investment in the long run. In contrast, bank-based financial development is found to have a negative accelerator enhancing effect on investment in the short run.
Keywords: G10; G20; E22; 330; South Africa; Investment; Bank-based financial development; Market-based financial development; Flexible accelerator model